1977
DOI: 10.1128/iai.16.3.773-780.1977
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins as Factors in the In Vitro Interaction Between Oral Streptococci in Plaque

Abstract: The effect of bacteriocins on the composition of dental plaque flora was studied in vitro with bacterial plaque formed by oral streptococci on glass rods suspended in broth medium. Cell-free preparations containing mutacin SW31, a bacteriocin produced by Streptococcus mutans , killed sensitive cells present in the plaque selectively, but did not affect resistant cells. Similar preparations from a non-bacteriocinogenic mutant exerted only a slight effect. Mixed growth of bacteriocin-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

1979
1979
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Microorganisms. The following strains of S. mutans were used: T2 (7); T2 bac-, a non-bacteriocinogenic mutant isolated after treatment of the parent strain with N-methyl-N'-nitro-N-nitroso-quanidine (Aldrich) (8); and SW31 (12) and its corresponding mutant, SW31 bac.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms. The following strains of S. mutans were used: T2 (7); T2 bac-, a non-bacteriocinogenic mutant isolated after treatment of the parent strain with N-methyl-N'-nitro-N-nitroso-quanidine (Aldrich) (8); and SW31 (12) and its corresponding mutant, SW31 bac.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggested that bacteriocins may play a role in modifying the plaque microflora. Recent in vitro experiments with a strain of S. mutans and a corresponding bac mutant have strengthened such a view (12).…”
mentioning
confidence: 99%
“…The consistent failure to demonstrate the actions of colicins in vivo probably results from their inactivation by proteases (Kelstrup & Gibbons 1969). More recent work suggests that bacteriocin activity is of great importance for organisms colonizing solid surfaces (Weerkamp et al 1977) especially in the mouth (Van der Hoeven & Rogers 1978. Indeed, the majority of the evidence supporting the selective advantage of colicin activity comes from observations of extra-intestinal environments (Konisky 1978).…”
Section: (Iii) Colicinsmentioning
confidence: 99%
“…Another observation indicating that mutacins have relatively little effect in the oral cavity is that both tnutacinogenic and sensitive strains can be isolated from the same dental plaque (16). This observation, and the fact that mutacins are seldom detected in liquid cultures (2,16,(20)(21)(22)(23)(24)(25), is probably an indication of a relatively restrained distatice over which they tnay act (26,27). Many in vivo experiments in humans and animals indicate that certain tnutacins decrease the number of S. tnutans in dental plaque and reduce the amount of caries (28-33), thus demonstrating a protective role for mutacins in the dental plaque ecosystem.…”
mentioning
confidence: 99%